Impacts of Racket Handle Design on Table Tennis Topspin Forehand Rally Performance Among Beginner Players - Ryushi Kumamoto; Ping Yeap Loh; Yuqi He; Enrico Ferlinghetti; Matteo Lancini; Tadashi Uno (Sports)
Physical inactivity is a major global public health concern, and table tennis offers a low-impact, engaging way to promote physical activity across various age groups. However, many beginners struggle to maintain effective participation due to their lower skill levels. Therefore, the development and reinforcement of stable grip techniques is crucial because it will help beginners achieve sustainable improvements in performance. This will provide additional opportunities to increase physical activity, and therefore overall health, across all age groups. Thus, in this study, we investigate the effects of a prototype table tennis handle on the racket angle and performance of beginners. The prototype handle features a 20° tilt to assist the player in maintaining a stable topspin forehand grip during play. The participants were randomized into three groups, Groups A, B, and C, which used the prototype handle, standard handle, and practiced with the prototype but performed tests with the standard handle, respectively. The participants executed topspin forehand strokes in approximately 30 min of practice, and data on racket angles, swing mechanics, success rates, and ball landing positions were collected. The results showed that Group A exhibited a larger racket open angle and a smaller racket face Angle than the other groups. However, the groups showed no significant differences in hit positions or overall success rates. Our results suggest that although the prototype handle can influence racket angles and some performance aspects, individual differences and swing mechanics should be considered.